SWOT Analysis Marketing Strategy In Creating A Competitive Advantage Home Industry Handicraft Folding Mat (Studies on CV. Excellent Group) - siti musarofah; Ardiansyah AH; Imam Kusnanto; Sawabi Sawabi (International Journal of Economics, Business and Innovation Research, 2022)
This study aims to analyze marketing strategies using SWOT analysis to create a competitive advantage in the folding mat home industry. This study was carried out at CV. Excellent Group in Kemendung Hamlet, Jatirejo Village, Tikung District, Lamongan Regency. The type of research used is descriptive qualitative. Data collection methods include interviews, observation, and a review of the literature. Interviews were conducted with company leaders and mat distributors. Analyze the data using IFAS, EFAS, and SWOT matrices. The results of the SWOT analysis show that the strength gets a score of 2.23 while the weakness gets a score of 0.54. Strength gets a higher score than weakness, with a difference of 1.69. Furthermore, opportunities get a score of 1.71 while threats get a score of 1.09. Opportunities get a higher score than threats, with a difference of 0.62. Based on the results of the internal and external matrix analyses, it is clear that a suitable strategy for the CV folding mat industry exists. Excellent is a Strengths-Opportunities (S-O) strategy, namely a strategy using strengths to take advantage of the opportunities owned by the company. improving the quality of products and services will increase the company's capacity by utilizing the ability of teamwork and company experience to reach potential markets.